Conducive Work Environment to Enhance Employee Performance in Umrah Service Companies - Utama, Indra; Riani, Asri Laksmi (The Eastasouth Management and Business, 2025)
This study investigates the impact of a conducive work-environment on employee performance within Umrah service companies in Indonesia. Drawing on Social Exchange Theory, it addresses a gap in the literature by integrating spiritual and professional dimensions unique to religious travel services. A quantitative, cross-sectional survey was administered to 300 employees, of which 280 valid responses were retained. Constructs included workspace design, leadership style, peer relations, supportive facilities, training and development, and work-life balance, measured via a six-point Likert scale. Data were analyzed using PLS-SEM with SmartPLS 4.0. Results indicate that the overall work-environment construct exerts a strong, positive, and significant effect on performance (β = 0.654, t = 10.021, p < 0.001), explaining 42.8% of its variance (R² = 0.428). Sub-dimension analysis highlights transformational leadership and peer relations as key drivers of performance, while ergonomic and spiritual facilities contribute to employee well-being and task effectiveness. High composite reliability and validity metrics confirm the robustness of the measurement model. Practical recommendations for HR managers include optimizing physical design, fostering team cohesion, providing dedicated worship and rest spaces, and enhancing leadership training. Limitations include the cross-sectional design and reliance on self-reported data; future research should adopt longitudinal and mixed-methods approaches, and extend comparisons across multiple countries.